QIBLA DIRECTIONS THROUGH ULAMA’S FATWA : Comparative Study between Qibla Direction Fatwa of Indonesian Ulama Council and Dar Al-Ifta Al-Misriyyah - Ahsin Dinal Mustafa (Fakultas Syari'ah dan Hukum UIN Walisongo, 2019)
Qibla direction is one of the important things in Islam. Especially in the prayer worship. Al-Quran and Hadith have explained about the direction of qibla during the lifetime of the Prophet. The Problems begun when Muslims spread all the world as it is today. Muslims who are far from Mecca can not see the Ka’bah, so it is difficult to determine the